The Choice of Codes among Santri in Communication through Facebook - Susylowati, Eka (Lingual Journal of Language and Culture, 2020)
The era of modernization of social media has always been associated with teenagers, especially those on Facebook. This social media can be used as a medium to show their existence. The language used for communication interactions varies. The purpose of this study is to identify the choice of language codes used by students in the Islamic Modern Assalaam Islamic Boarding School in Indonesia in their communication interactions. This research is a qualitative in nature. The data under investigation are students’ conversations on Facebook, which are particularly related to the choice of codes. Data collection includes observation, field notes, and interviews. This research analysis employs the components of the Hymes (SPEAKING) speech. The research results demonstrate that the choice of language codes used by students to communicate in social media involves Indonesian, Arabic, English, and Javanese. The development of technology can make communication effective for students. Besides, that can drive the changes in behavior and language they use. The significance of this research is that there are bilingualism/multilingualism phenomena through the use of Indonesian, Arabic, and English, which is proven not to shift the local language (Javanese), let alone destroying local language as a mother tongue.